Protection of women's rights in Africa through national human rights institutions (NHRIs) : a case study of Ghana and the Republic of South Africa - Appiagyei-Atua, Kwadwo (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.